Ensembled Geometric Semantic Genetic Programming: An ensemble-based initialization technique for Geometric Semantic Genetic Programming - Rosenfeld, Liah (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics